Super searchers make it on their own : top independent information professionals share their secrets for starting and running a research business - Sabroski, Suzanne, 1965- (Super searchers, 2002)
Offering the advice, insights, experiences, and encouragement would-be Internet entrepreneurs need to establish a successful independent research business, this book provides an insider's view of Internet businesses and their unique services. Eleven entrepreneurial super searchers representing a broad range of topic specialties and business focuses are interviewed. Also discussed are the details for getting started, developing a niche, finding clients, doing the research, networking with peers, and staying well informed about Web resources and technologies.